(untitled) - Food and Agriculture Organization of the United Nations,World Health Organization (Rome, 2008)
The Codex Committees on Meat Hygiene, Processed Meat and Poultry Products, Residues of Veterinary Drugs in Foods and Food Additives and Contaminants and the ad hoc Task Force on Animal Feeding have developed texts on meat hygiene, animal feeding and antimicrobial resistance. Includes the Code of Hygienic Practice for Meat; the Code of Practice on Good Animal Feeding; a Glossary of Terms and Definitions (Veterinary Drugs Residues in Foods), and more. This first edition includes all texts adopted by the Codex Alimentarius Commission up to 2007.
Keywords: Ngành công nghiệp thịt và thương mại,Meat hygiene,Food of animal origin,Meat industry and trade,Vệ sinh thức ăn,Thực phẩm từ động vật; Tiêu chuẩn,Standards,Standards,Standards,Tiêu chuẩn,Tiêu chuẩn